IMPROVING TUNA GRAHITA STUDENTS’ VOCABULARY MASTERY BY USING ENGLISH SONGS IN TEACHING AND LEARNING ENGLISH - Eva Yunita Indraswari (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2018)
Teaching vocabulary mastery means giving instruction to the students to learn about vocabulary in English so they will know or understand the vocabulary of songs. Vocabulary mastery should get more attention because there are many Tuna Grahita students’ who get information and difficulties in learning. The objective of the research is to find out if there is significant difference of the vocabulary mastery achievement of the eighth graders of SMPLB Negeri Jepara between before and after being taught by using English songs. The design of this research was pre-experimental research which used pre-test and post –test. The population of this research is the Tuna Grahita class which consist of 44 students. The samples are the students of eighth grade, the instruments of test is oral or speak, multiple choices test and colouring draw. The result of this research showed that the result of pre-test was categorized as sufficient. The score of mean and standard deviation were 60,5 and 21,39 meanwhile , the result of post test was categorized as good. The score of mean and standard deviation were 70,8 or 71 and 17,87. The calculation of t-test got 2,42 with the level of significant 0.05 or 5% and (df) 12. It was concluded that there is a significant difference between vocabulary mastery achievement for the eighth graders students of SMPLB Negeri Jepara before and after being taught by using English songs.